The international climate change regime : a guide to rules, institutions and procedures / Farhana Yamin and Joanna Depledge. - Yamin, Farhana; Depledge, Joanna (Cambridge University Press, 2004)
This book presents a comprehensive, authoritative and independent account of the rules, institutions and procedures governing the international climate change regime. Its detailed yet user-friendly description and analysis covers the UN Framework Convention on Climate Change, the Kyoto Protocol, and all decisions taken by the Conference of the Parties up to 2003, including the landmark Marrakesh Accords. Mitigation commitments, adaptation, the flexibility mechanisms, reporting and review, compliance, education and public awareness, technology transfer, financial assistance and climate research are just some of the areas that are reviewed. The book also explains how the regime works, including a discussion of its political coalitions, institutional structure, negotiation process, administrative base, and linkages with other international regimes. In short, this book is the only current work that covers all areas of the climate change regime in such depth, yet in such a uniquely accessible and objective way.